Illegally Blonde: The Racialisation of Blondness and Visual Representations of Palestinian Activist Ahed Tamimi in American and Canadian Media - Wang, Kuan-Yun (Journal of Holy Land and Palestine Studies, 2020)
Informed by theories of media representation, Orientalism, and settler colonialism, this research endeavours to contribute to the discussion on the impact of media representation within a specific political context. It intends to reveal the power dimensions and ideological positions embedded in dominant media discourses in North America. Five news videos, three from Canadian, and two from American online daily media sources, are selected carefully during December 2017 and July 2018 when the Israeli army arrested Ahed Tamimi. In terms of methodologies, adopts Chouliaraki's (2011) multimodality model to analyse the visual and semiotic choices made by the news editors and draws on Fairclough's (1995) conception of Critical Discourse Analysis (CDA) for its contextual analysis. The findings suggest that through different discursive and representational strategies, the media frame Tamimi and the Palestinians as violent initiators. Moreover, Tamimi's blondness and her Western' look are marked as fake' and propaganda', thus establishing the new norm of representing Otherness'. These strategies echo accepted values in American and Canadian societies and their foreign policies in the past decade. The results also achieve the purpose of legitimising the use of state violence on colonised bodies, which ultimately reflects settler-colonial history in North America.